Nanoparticles for Biomedical Use Derived from Natural Biomolecules: Tannic Acid and Arginine - Mehtap Sahiner; Selin S. Suner; Nurettin Sahiner (Biomedicines)
Background/Objectives: Tannic acid (TA) is a well-known natural phenolic acid composed of ten gallic acids linked to each other with ester bonding possessing excellent antioxidant properties in addition to antimicrobial and anticancer characteristics. Arginine (ARG) is a positively charged amino acid at physiological pH because of nitrogen-rich side chain. Method: Here, poly(tannic acid-co-arginine) (p(TA-co-ARG)) particles at three mole ratios, TA:ARG = 1:1, 1:2, and 1:3, were prepared via a Mannich condensation reaction between TA and ARG by utilizing formaldehyde as a linking agent. Results: The p(TA-co-ARG) particles in 300–1000 nm size range with smooth surfaces visualized via SEM analysis were attained. Abundant numbers of functional groups, -OH, -NH2, and -COOH stemming from TA and ARG constituent confirmed by FT-IR analysis. The isoelectric point (IEP) of the particles increased from pH 4.98 to pH 7.30 by increasing the ARG ratios in p(TA-co-ARG) particles. The antioxidant capacity of p(TA-co-ARG) particles via gallic acid (GA) and rosmarinic acid (RA) equivalents tests revealed that particles possess concentration-dependent antioxidant potency and increased by TA content. The α-glucosidase inhibition of p(TA-co-ARG) particles (2 mg/mL) 1:1 and 1:2 mole ratios revealed significant enzyme inhibition ability, e.g., 91.3 ± 3.1% and 77.6 ± 12.0%. Interestingly, p(TA-co-ARG) (1:3 ratio) possessed significant antibacterial effectiveness against Escherichia coli (ATCC 8739) and Staphylococcus aureus (ATCC 6538) bacteria. Furthermore, all p(TA-co-ARG) particles at 1000 mg/mL concentration showed >80% toxicity on L929 fibroblast cells and increased as ARG content of p(TA-co-ARG) particles is increased. Conclusions: p(TA-co-ARG) showed significant potential as natural biomaterials for biomedical use.